FORMULATION AND EVALUATION OF DEXTROMETHORPHAN HYDROBROMIDE CONTROLLED RELEASE HOLLOW MICROSPHERES USING NATURAL POLYMER - C, Sai Sathavahana (Indonesian Journal of Pharmacy, 2014)
The objective of this study was to formulate and evaluate gastric floating dosage forms of hollow microspheres for controlled delivery of dextromethorphan hydrobromide (DBM). Hollow microspheres were prepared by emulsion polymerization method using natural polymer gelatin as release retardant and coating agent. Hollow microspheres were characterized by FT-IR, DSC, SEM, and micromeritic properties. FT-IR and DSC studies showed no chemical interaction between the drug and polymers. Hollow microspheres were evaluated for percentage yield, encapsulation efficiency and in vitro release studies. The obtained angle of repose, % Carrâ€™s index, Hausner ratio, and tapped density values were within the limits indicating good flow properties. The surface morphology revealed that microspheres were spherical with minute pores and invert dents on the surface. Among all the formulations, F-3 of hollow microspheres showed highest drug release of 79.69Â±0.12% at the end of 12h which was considered as the best formulation. The release data was fitted to various mathematical models such as, Higuchi, Korsmeyer-Peppas, First-order, and Zero order to evaluate the release kinetics and mechanism of the drug release. The release kinetics indicated that drug release followed non-fickian diffusion mechanism. Results of the stability studies showed that there were no significant changes in the drug content and physical appearance.Â